Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti dengan Model Problem Based Learning (PBL) Berbantuan Video Animasi Materi Manusia sebagai Citra Allah Fase D Kelas VII di SMP Negeri 6 Sanggau - Victorina Lidia Novianty; Yusmanto Yusmanto; Busri Busri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve the learning outcomes of grade VII students on Human material as the Image of Allah through the Problem Based Learning (PBL) model at SMP Negeri 6 Sanggau which is carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The research subjects in this observation are 37 students in grade VII of SMP Negeri 6 Sanggau. Data collection techniques are carried out through tests (formative tests) and non-tests (observation). The results of the research on the affective aspect of students in cycle I showed an average percentage of 70% increased by 8% to 78% in cycle II. In the first cycle, the percentage of learning outcomes for students in the advanced category was 1%, capable 3%, feasible 24% and newly developed 9%. Meanwhile, in the second cycle, there was an increase in the advanced category of 8%, capable 12%, decent 17% and just developed 0%. So, it can be concluded that learning Catholic Religious Education and Ethics with the Problem Based Learning (PBL) method is proven to improve student learning outcomes. In addition, this learning model can also increase students' confidence, especially in developing communication skills in groups and with educators.